Reactive oxygen species promote chloroplast dysfunction and salicylic acid accumulation in fumonisin B1‐induced cell death. Issue 14 (24th May 2013) - Xing, Fuqiang; Li, Zhe; Sun, Aizhen; Xing, Da
Abstract : We report a novel regulatory mechanism by which reactive oxygen species (ROS) regulate fumonisin B1 (FB1)‐induced cell death. We found that FB1 induction of light‐dependent ROS production promoted the degradation of GFP‐labeled chloroplast proteins and increased phenylalanine ammonia lyase (PAL) activity, PAL1 gene expression and SA content, while pretreatment with ROS manipulators reversed these trends. Moreover, treatment with H2 O2 or 3‐amino‐1, 2, 4‐triazole increased PAL activity, PAL1 gene expression and SA content. PAL inhibitor significantly blocked FB1‐induced lesion formation and SA increase. Our results demonstrate that light‐dependent ROS accumulation stimulates the degradation of chloroplastic proteins and up‐regulates PAL‐mediated SA synthesis, thus promoting FB1‐induced light‐dependent cell death. Abstract : Light‐dependent ROS production is associated with FB1‐induced cell death. ROS cause chloroplast dysfunction in response to FB1 treatment. ROS promote SA synthesis via PAL‐mediated signaling pathway in FB1‐induced cell death.